THE INFLUENCE OF CUTTING SPEEDS ON TURNING AISI 1018 STEEL USING CEMENTED CARBIDE INSERT - HASSAN, MOHD NOR HAKIM; AHMAD BAKIR, AZMAN (MALAYSIAN JOURNAL OF INNOVATION IN ENGINEERING AND APPLIED SOCIAL SCIENCES (MYJIEAS), 2024)
ABSTRACT - This research investigates the influence of cutting speed and feed rate on the wear performance of cemented carbide inserts during tuning operations on AISI 1018 steel. Understanding the interplay between cutting speed, tool wear, and surface roughness is crucial for optimizing machining processes, ensuring tool longevity, and achieving desired surface quality. The study employed three distinct cutting speeds (660, 870, and 1400 rpm) and two different feed rates (0.23 and 0.34 mm/rev) while maintaining a fixed depth of cut (1 mm). The width of the flank wear on the inserts, was measured using a digital microscope and Image J analysis software after each single machining run until it reached 20 reading. Surface roughness of the new machined workpieces was evaluated using a surface roughness tester. Results reveal that higher cutting speeds lead to faster flank wear, reducing tool life. While all cutting speeds resulted in average surface roughness values exceeding 1.6 um, the lower feed rate exhibited a better surface finish compared to the higher one. The cutting speed of 131.19 m/min (870 rpm) and a feed rate of 0.23 mm/rev demonstrated the most moderate wear and machining time, making it a potential candidate for optimized turning operations in this setting.